1975
DOI: 10.3758/bf03204097
|View full text |Cite|
|
Sign up to set email alerts
|

Persistence and integration: Two consequences of a sliding integrator

Abstract: The detection of a silent interval, or gap, placed in the temporal center of a gated noise burst was investigated. The gated noise masker ranged from 2 to 400 msec in duration. For long noises, the duration.a. of the just-detectable gap remained fixed at about 2.8 msec. Progressively shortening the duration of the noise did not affect A until the duration was approximately 20 msec; thereafter. decreasing the noise duration improved detectability of the gap. In a second experiment, continuous noise filled the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 11 publications
2
28
1
Order By: Relevance
“…The present data indicate that for the rat, the shortest detectable gap had a duration of 2 msec when presented with a very brief rise-fall time. The 2-msec figure found here is consistent with other estimates of the limit of temporal acuity in the mammalian auditory system (see, e.g., Forrest & Green, 1987;Penner, 1975).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The present data indicate that for the rat, the shortest detectable gap had a duration of 2 msec when presented with a very brief rise-fall time. The 2-msec figure found here is consistent with other estimates of the limit of temporal acuity in the mammalian auditory system (see, e.g., Forrest & Green, 1987;Penner, 1975).…”
Section: Discussionsupporting
confidence: 81%
“…It has been proposed that the limit of the auditory system's ability to resolve temporal detail is imposed by the extent to which the time course of neural activity outlasts the physical stimulus that initiated the activity (see, e.g., Penner, 1975;Plomp, 1964). The detectabi1ity of a gap would therefore be determined by the rate of decay of such neural activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the temporal interval needed for one to hear two auditory signals as distinctly separate is a linear decreasing function of signal duration. Similarly, Penner (1975) found that for marker durations ranging from I to 10 msec, detection of an empty interval improved with decreasing marker duration; with marker durations ranging from 30 to 200 msec, however, detection of empty intervals was no longer affected.…”
mentioning
confidence: 96%
“…Moreover, Kellogg, Ison, and Miller (1983) reported that prenatal diazepam exposure in rats retarded the development of auditory temporal resolution, as indexed by the effectiveness of acoustic gaps as startle inhibitors. It is of special interest that Ison and Pinckney (1983) reported that the minimum gap required to reliably produce inhibition of an elicited eyeblink in humans (again approximately 4 msec) corresponds to the values reported in various assessments of the threshold for gap detection, as measured with standard psychophysical procedures (Penner, 1975;Perrott & Williams, 1971;Plomp, 1964;Smiarowski & Carhart, 1976;Williams, Elfner, & Howse, 1979).…”
Section: Tonal Frequency Shifts and Gaps In Acoustic Stimulation As Rmentioning
confidence: 99%